Biblical Women Speak : Hearing Their Voices through New and Ancient Midrash - Feldman, Marla J. (Book collections on Project MUSE., 2023)
"Biblical Women Speak employs midrash (interpretive techniques) to discover ten biblical women's stories from a female point of view and provide insights beyond how ancient male scholars viewed them"--